Two new species of freshwater flatworms (Platyhelminthes: Tricladida: Continenticola) from South American caves - Souza, Stella; Morais, Ana Laura; Bichuette, Maria Elina; Leal-Zanchet, Ana (Zootaxa, 2016)
The diversity of freshwater triclads in the Neotropical region is considered to be low, but extensive areas of South America remain almost unexplored. Herein we describe two cave-dwelling, new species of Girardia, one from a transition zone of the Cerrado and Caatinga phytophysiognomies and the other from the Cerrado phytophysiognomy. The species from the Cerrado-Caatinga transition is a troglobite, eyeless and whitish; the species from the Cerrado area is possibly a troglophile, since it shows heavily pigmented body and eyes. Each species is easily recognized by a unique combination of features in its external morphology and copulatory apparatus. The two new species of Girardia show a restricted distribution, even the troglophile, and occur in caves without legal protection. Therefore, they must be considered as vulnerable organisms in a conservation context.